Manual Vacuum Aspiration versus Sharp Curettage for Incomplete Abortion: Which One is Better? Aspirasi Vakum Manual dibandingkan dengan Kuret Tajam untuk Abortus Inkomplit: Mana yang Lebih Baik? - JM Seno Adjie; Erik J Triyadi (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective: To acknowledge the effectiveness and safety of MVA compare with SC in management of incomplete abortion below 12 weeks of gestation which compare time to perform procedure, rates of evacuation and infection one week after procedure, and complication during MVA and SC procedure Methods: A prospective study with 62 subjects with complain incomplete abortion came to ER at RSCM, RS Fatmawati and RS Karawang, divided into 31 subjects on MVA group and 31 subjects on SC group. The data was documented on the time of MVA procedure compare to SC, clinical findings on complication during procedure, completed evacuation and infection symptoms one week after procedure. Results: Sixty two subjects (31 each group) with average time of procedure was 17,65 ± 4,128 minutes and SC was 22,26 ± 4,611 minutes with p = 0,00 and 95% CI; -4,513(-6,837 to -2,389 with significant statistically difference. The comparison of completed evacuation one week after procedure was 3,2% (n = 1) on MVA and 6,5% (n = 2) on SC with clinical findings, and p = 0,554, RR = 1,034 and 95% CI 0,924 – 1,158 with no statistically difference. On the other comparison, we didn’t find any infection symptoms one week after procedure and complication during procedure on both of procedures. Conclusion: MVA has more effective than SC on the time of procedure in incomplete abortion with below 12 weeks of gestation. MVA has superiority from completed evacuation but no statistically difference and has equal safety to SC on clinical infection symptoms and complication during procedure. Keywords: Manual Vacuum Aspiration (MVA), sharp curettage (SC), incomplete abortion. Tujuan:Mengetahuiefektifitasdankeamanandari AVM dibandingkan dengan kuret tajam pada penanganan abortusin komplit dibawah usia kehamilan 12 minggu dengan melihatdari lama tindakan, proporsi tingkat kebersihan evakuasi sisa konsepsi 1 minggu pasca tindakan, proporsigejala – gejalainfeksi 1 minggu pasca tindakan dan proporsi komplikasi pada saat tindakan AVM dan kuret tajam. Metode:Penelitian ini merupakan penelitian kohort prospektif (observasional) dengan jumlah sampel 62 subjek yang berkunjung dengan abortusin komplit ke UGD RSCM, RS Fatmawati dan RSUD Karawang terbagi dalam 31 subjek pada kelompok prosedur AVM dan 31 subjek pada kelompok prosedur kuret tajam. Data dikumpulkanmelaluipencatatanwaktu lama prosedur AVM dibandingkankurettajam, pemeriksaan klinis komplikasi selama prosedur berlangsung, pemeriksaan klinis kebersihan sisa konspesi 1 minggu pasca tindakan dan gejala – gejala infeksi 1 minggu pasca tindakan. Hasil:Sebanyak 62 subjek (masing – masing 31 subjek), dimana didapatkan rerata dan simpang baku prosedur AVM 17,65 ± 4,128 menit dan kuret tajam 22,26 ± 4,611 menit dengan p = 0,00 dan IK 95% -4,513(-6,837 s/d -2,389), bermakna secara statistik. Pada perbandingan proporsi tingkat kebersihan evakuasi sisa konsepsi 1 minggu pasca tindakan didapatkan pada AVM 3,2% (n = 1) dan pada kuret tajam 6,5% (n = 2) terdapat sisa konsepsi dengan penilaian klinis, p = 0,554, RR = 1,034 dan IK95% 0,924 – 1,158 tidak memiliki perbedaan bermakna secara statistik. Pada perbandingan lainnya, tidak ditemukan gejala – gejala infeksi 1 minggu pasca prosedur dan komplikasi selama prosedur berlangsung pada prosedur AVM dan kuret tajam. Kesimpulan:.AVM juga memiliki keunggulan dalam kebersihan sisa konsepsi namun tidak bermakna secara statitik dan memiliki keamanan yang setara dengan kuret tajam dari tingkat gejala infeksi dan komplikasi selama prosedur. Kata kunci :Aspirasi Vakum Manual (AVM), kuret tajam, abortusin komplit